THE EFFECT OF CORPORATE SUSTAINABILITY ON THE FINANCIAL PERFORMANCE OF MANUFACTURING SECTOR COMPANIES IN THE BIST SUSTAINABILITY INDEX (Third Sector Social Economic Review, 2021)
Sustainability is meeting today's needs without giving up the environmental, economic and social existence and improvement of the world. The importance of corporate sustainability, which can be expressed as creating value in the long term, has increased by integrating the elements of sustainability into companies' activities and decision-making processes. However, from the perspective of companies, whether the corporate sustainability performance of companies is related to their financial performance has started to be a subject that has been investigated in the literature. In this study, using the BIST Sustainability Index as a representative of corporate sustainability performance, the impact of corporate sustainability performance on financial performance has been analyzed for 4 manufacturing companies included in the index since the date the index was calculated (November 2014). In the analysis made using the TOPSIS method, it was concluded that the performance of 3 companies increased and 1 of the companies decreased in the post-index period compared to the pre-index period.
Keywords: Sustainable Development; Corporate Sustainability; Sustainability Performance; Sustainability Index; Manufacturing Industry